"Lucy says today she is a Labordoodle": how the dogs-of-Instagram reveal voter preferences. Issue 4 (8th August 2019) - Caple, Helen
ABSTRACT: Instagram is an image-centric social media application, launched in October 2010 with the explicit aim of allowing members to share their smart phone photos with the world. Posts typically combine photographs with a short verbal text, and as such provide fertile ground for multisemiotic analysis. Further, at times of political significance or upheaval, Instagram, like other social media platforms, provides a space for the public to express opinions or emotions. The fact that citizens do this through a combination of words and images on Instagram is the subject of analysis in this article. Using a dataset of 92 Instagram posts that made use of the discourse tagging hashtag #dogsatpollingstations at the time of the 2016 Australian federal election, this study demonstrates the multisemiotic strategies used by members of the public to show their dissatisfaction with the incumbent government, and their endorsement of other political parties. The study also demonstrates the triangulation of multiple methods, and as such is an example of corpus-assisted multimodal discourse analysis.